La política educativa y su compromiso con la equidad social y el desarrollo sostenible - Torres Victoria, Nancy (2010)
The article centers its analysis in two areas of the current educational policies in Costa Rica: the statements that the document contains about its commitment with the social equity and the sustainable development, subject that has a strong relationship with rural education, its conceptualization, its planning, and its development. At the same time, it traces a brief description of the development of the right to education in the nation’s politics, showing advances of the country’s vulnerable groups, with the promulgation of new laws that these sectors have been reaching through fights and organized demands.